Possibilities and limitations of thromboelastometry/thromboelastography - Lang, T.; Depka, von M. (Hämostaseologie, 2006)
Thromboelastometry/thromboelastography provides information about clot strength and stability. Modified procedures have improved the standardisation and increased the diagnostic power of these test systems. Heparinase- modified thromboelastometry/thromboelastography allows assessment of the heparin effect. The introduction of FIBTEM on the ROTEM® also makes it possible to differentiate between disorders of the plasma and platelet components of clot strength. This may be of interest in the perioperative setting, as our clinical data show that elevated levels of D-dimer have no predictive value for hyperfibrinolysis.However, disorders of primary haemostasis such as von Willebrand’s disease cannot be determined with thromboelastometry/ thromboelastography, nor do the effects of acetyl salicylic acid and clopidogrel on platelets influence the results. Only platelet aggregation inhibitors which affect the glycoprotein IIb/IIIa receptors, such as ReoPro®, may reduce clot strength at high doses. A similar effect is to be expected with severe Glanzmann’s thrombasthenia. Coagulation times in thromboelastometry/thromboelastography (measured as CT/r value) show poor correlation with conventional coagulation parameters because of the different activators used.The introduction of rotation thromboelastometry (ROTEM®) provides a stable system suitable for near patient testing.
Keywords: Thrombelastometry; thrombelastography; ROTEM; TEG